Perbedaan Daya Antibakteri Antara Kombinasi Calcium Hydroxide-Based Sealer-Amoxicillin Dan Resin-Based Sealer-Amoxicillin Terhadap Bakteri Enterococcus Faecalis - Asarizka Bena; Agus Subiwahjudi; Setyabudi Setyabudi (Conservative Dentistry Journal, 2018)
Background. About 24-77% of root canal treatment failure cases are caused by infection of Enterococcus faecalis due to the resistance factor and virulence of these bacteria. Calcium hydroxide-based sealer and resin-based sealer are two types of sealer often used for root canal obturation due to their antibacterial properties. But the antibacterial properties owned by calcium hydroxide-based sealer has no effect on Enterococcus faecalis. Therefore, the adjunct of local antimicrobial such as amoxicillin is needed to increase antibacterial activities of root canal obturation materials (sealers) especially for calcium hydroxide-based sealer. Purpose. The aim of this study was to compare the effectiveness of antibacterial activity of calcium hydroxide-based sealer-amoxicillin and resin-based sealer-amoxicillin against Enterococcus faecalis. Methods. This study is an experimental laboratory with post test only control group design using Enterococcus faecalis ATCC 29212. Agar diffusion test was used to check the antimicrobial activity of calcium hydroxide-based sealer-amoxicillin and resin-based sealer-amoxicillin. by measuring the inhibition zone diameter of each treatment. Results. Resin-based sealer-amoxicillin’s diameter of zone inhibition is 37,3 mm and calcium hydroxide-based sealer-amoxicillin’s diameter is 18,7 mm. Conclusion. Antibacterial activity of resin-based sealer-amoxicillin is significantly greater than calcium hydroxide-based sealer-amoxicillin.